Theoretical Investigation of Backward Optical Parametric Oscillator Pumped by Vortex Beams - Zhu, Xiaosi; He, Jianlang; Su, Yawen; Chen, Yan; Hu, Xiaopeng (Frontiers in Physics, 2022)
Nonlinear generation and manipulation of vortex beams have been emerged as a research hot topic in recent years. During the nonlinear frequency conversions, the orbital angular momentum will transfer from the fundamental wave to the harmonic waves. In this work, we study theoretically the backward optical parametric oscillator pumped by vortex beams. The orbital angular momentum conservation law has been disclosed for the counter propagation nonlinear process. In addition, the oscillation threshold and the conversion efficiency have been investigated in detail. Our results will be helpful to the experimental demonstration of backward optical parametric oscillator pumped by vortex beams.